The Effect of Nanoparticles Andrographis paniculata (Sambiloto) Extract on IL-10 and TNF-α Levels in Wistar Rats Infected with Listeria monocytogenes - Ulfa, Firdanianti; Farida, Helmia; Susilaningsih, Neni (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: World Health Organization (WHO) determines Listeria monocytogenes as one of the four major bacteria that cause foodborne disease. During L. monocytogenes infection, TNF-α with IFN-γ activates macrophages for the inflammatory process. In the middle of infection, NK cells produce IL-10 to prevent excessive inflammation. Andrographis paniculata (sambiloto in Indonesia) has been known as a traditional medicine for generations. It has been previously known that administration of A. paniculata to mice with rheumatoid arthritis showed an increase in IL-10 cytokine activity in spleen samples. In addition, it also downregulates the production of inflammatory mediators such as Nitric Oxide (NO) and TNF-α. The extracts are converted into nano-sized particles to be easily absorbed by cells, thus allowing the delivery of active substances to the targeted location. This study aims to determine A. paniculata's effect on IL-10 and TNF-α cytokines in rats infected with L. monocytogenes.Methods: This study used 30 male Wistar rats infected with L. monocytogenes (except in the normal group). The animals were divided into 6 groups, i.e. Normal group, Negative Control group (K-), EAP200, nEAP100, nEAP200, and nEAP400. Crude extract of A. paniculata 200 mg/kg BW, nanoparticles of A. paniculata extract 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW were administered for 7 days to the EAP200, nEAP100, nEAP200, and nEAP400 groups, respectively.Results: The IL-10 and TNF-α levels in EAP200, nEAP100, nEAP200, and nEAP400 were significantly lower than the K- group. The lowest levels of IL-10 and TNF-α were in the nEAP400 group.Conclusion: Administration of A. paniculata extract nanoparticles decreased IL-10 and TNF-α levels in infected Wistar rats. The lowest levels of IL-10 and TNF-α were found in the nanoparticle group which received 400 mg/kg BW.